Students' Critical Thinking Abilities in Solving HOTS Questions on Circles - Muhammad Razali; Yulia Tiara Tanjung (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Critical Thinking is the ability to think rationally and see problems objectively so that the results obtained are unusual and in accordance with existing reality. HOTS is a process of thinking of students at a higher cognitive level developed from various cognitive concepts and methods and learning taxonomies such as the problem-solving method, Bloom's taxonomy, and the taxonomy of learning, teaching, and assessment. This study uses a descriptive qualitative approach, which aims to analyze students' critical thinking skills in solving mathematics problems. This study was conducted in August 2024 at SMP IT Daarul Istiqlal. This study took a sample of grade VIII, namely 30 students. Furthermore, students will be classified based on the level of high metacognitive ability, medium metacognitive ability and low metacognitive ability according to the results of the analysis of student answers. Grouping categories of high, medium and low metacognition. Subjects were selected based on considerations of availability and relevance to the research objectives. Data collection techniques used were using questions or tests, interviews, questionnaires and documentation. Documentation is a qualitative data collection technique in the form of printed, written data and recordings in answering questions. This data analysis technique uses three stages: data reduction, data presentation, and drawing conclusions. The results of the data analysis are specifically organized and presented descriptively.